Fast forwarding Higher Education Institutions for Global Challenges Perspectives and Approaches - Amzat, Ismail Hussein; Yusuf, Byabazaire; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2016)
This book addresses various 21st century questions and challenges, especially the role of technology in upgrading teaching and learning in today$1 (Bs society, and the role of higher education institutions in improving standards of living, economics, society and sustainability. It shares with readers the challenges of globalization to higher institutions concerning the issues relating to value creation management, branding and the impact on leadership in higher institutions.s
Part 1 Fast-forwarding: the role of Educational Technology -- Chapter 1 Fast-tracking Technology Integration toward Global Education in Oman -- Chapter 2 Rich Text, Rich Teach expanding educational horizons with new technology -- Chapter 3 Open source pathways to educational development -- Chapter 4 Managing and evaluating ICTs in Higher Education: A reassurance measure for sustainable investment -- Chapter 5 Digital technologies and emerging educational objectives: The need for transformational changes in teacher education & training -- Part 2 Fast-forwarding: teaching & learning for Social Development -- Chapter 6 The transforming nature of teaching and learning in higher education: A University of South Pacific experience -- Chapter 7 Multiculturalism: The value of every individual in the Higher Education Institutions -- Chapter 8 Counselling Ethics Education: Teaching and Learning Development Reformation -- Chapter 9 E-Counselling modality in Higher Education Institutions of Malaysia -- Part 3 Role of Higher Institutions: Nation building & Sustainability -- Chapter 10 Transforming Brics to Brincs for faster economic growth in Nigeria: The role of tertiary educational institutions -- Chapter 11 Capacity building for Educational Leaders in an era of change: The role of Higher Education Providers -- Chapter 12 Caring: A useful tool for embedding sustainability into Nursing Education -- Part 4 Fast-forwarding: Globalization & Educational Leadership -- Chapter 13 Branding Higher Institutions: What it takes to be branded -- Chapter 14 Knowledge Development, ICT Management and Education Policy: Global Issues, Local Challenges -- Chapter 15 Moral Sensitivity Practice in Academic Deanship: Does it really matter? -- Chapter 16 Improving the quality of Technical Education through International Standardization: The case of Coast Institute of Technology, Kenya.
Keywords: Education; Personnel management; International education; Comparative education; School management and organization; School administration; Education; Administration, Organization and Leadership; International and Comparative Education; Human Resource Management; Electronic books